Doodle.AI: Redefining creative play with human-AI competition in real-time doodle recognition - Ishan Panta; Biplov Paneru; Bishwash Paneru; Bipul Thapa (Systems and Soft Computing)
Doodle.AI is an innovative web-based game that takes creativity, guessing, and artificial intelligence and puts them together in a great combination. It is both an entertaining and educational game, enabling players to enhance their creativity and guessing skills while exploring AI capabilities interactively. The participants draw random words as they compete with an artificial intelligence model, which predicts drawings in real time. The AI component not only adds challenge and thrill but also demonstrates the capability of machine learning in interactive gaming. To create a highly precise doodle recognizer, a Long-term Recurrent Convolutional Network (LRCN) was employed, and it proved to be much better than the typical Convolutional Neural Networks (CNNs). The LRCN model achieved 90 % accuracy in the top-1 score and 97 % in the top-3 score, which is a measure of its high level of prediction. Relative to CNNs, which were overfitting (training loss: 36 %, validation loss: 53 %), LRCN demonstrated a substantial learning curve, stabilizing at a final loss of 39 %, thereby offering better resilience. Furthermore, LRCN outperformed CNN, and therefore particularly has been found useful in dynamic gaming conditions. Doodle.AI is more than just for fun, providing interesting commentary on the domain of AI-based sketch recognition and the viability of deep learning algorithms in real time. The wide variety of categories and questions in the game makes it an enjoyable experience, as users are challenged to sharpen their creativity and intellectual skills while engaging with advanced AI technologies.